2021
DOI: 10.1038/s41598-021-84204-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the choroidal structure in pregnant women in the first trimester

Abstract: We investigated the anatomical differences in the choroidal structure between pregnant women in the first trimester of pregnancy and age-matched healthy nonpregnant women using enhanced depth imaging optical coherence tomography (EDI-OCT) and choroidal binarization analysis. The main parameters measured in the two study groups, namely, pregnant women in the first trimester and healthy nonpregnant women, were choroidal thickness and the choroidal luminal area. Binarization of the EDI-OCT images from each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“… 14 Our previous study has suggested that the CVI was higher during the first trimester of pregnancy compared with healthy control participants, and that it was positively associated with SBP. 10 However, this study revealed no significant association between the CVI and SBP throughout pregnancy. This discrepancy may be due to the fact that some participants with pre-eclampsia could not undergo OCT measurement and blood sampling in late pregnancy because of premature birth.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“… 14 Our previous study has suggested that the CVI was higher during the first trimester of pregnancy compared with healthy control participants, and that it was positively associated with SBP. 10 However, this study revealed no significant association between the CVI and SBP throughout pregnancy. This discrepancy may be due to the fact that some participants with pre-eclampsia could not undergo OCT measurement and blood sampling in late pregnancy because of premature birth.…”
Section: Discussioncontrasting
confidence: 70%
“…Using the binarisation technique, we recently investigated the choroidal structure during the first trimester of pregnancy. 10 Our results showed that in the first trimester of pregnancy, the Choroidal Vascular Index (CVI) was higher compared with that of the non-pregnant women in the control group. In contrast, the CCT was not significantly different between the pregnant and control groups.…”
Section: Introductionmentioning
confidence: 56%
“…In the choroid, the flow per perfused volume is the highest of any other human tissue, and the choroidal vessels and capillaries contain about 85% of the overall ocular blood flow [ 19 ]. Therefore, its anatomy is mainly driven by ocular blood flow, which previous studies have shown to be altered in pregnant women [ 20 , 21 ]. Kara et al reported the choroid to be significantly thicker (about 35 µm) in pregnant women than in the non-pregnant controls [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kara et al reported the choroid to be significantly thicker (about 35 µm) in pregnant women than in the non-pregnant controls [ 22 ]. Correspondingly, Azuma et al evaluated the subfoveal choroidal vascularity index, which was significantly higher in the pregnancy group [ 20 ]. By contrast, in the current study, the SFCT was significantly thinner in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…No signi cant correlations was found between the subfoveal, temporal, nasal choroidal thickness and CMT(all P>0.05). pregnant and non-pregnant women [15,16]. Only the pregnant women in the rst or third trimester were enrolled in their study might attribute to this contradictory results.…”
Section: Correlations Analysismentioning
confidence: 99%